Differences in the Impact of the First Wave of the COVID-19 Pandemic on Student Employment in Selected EU Countries. Scale and Consequences - Izabela OSTOJ (Communications of International Proceedings, 2021)
The work-study combination has become increasingly common in many countries and attracts research on its causes and consequences. It continues to raise a lot of controversy, in particular due to the impact that employment has on the time allocated to studying. The COVID-19 pandemic has exerted an additional influence on the situation. The aim of the study is to determine the impact of COVID-19 on student employment in terms of its differences in selected EU countries. The article uses data from the global survey conducted by Covid-19 Social Science Lab, operating at the University of Ljubljana, and Eurostat data. The study confirms that the impact of the pandemic on student employment varies between countries to the degree much greater than it might be the result of the differences between major macroeconomic indicators in the countries under examination. Student job losses will cause that some students will neither be able to satisfy their material needs, nor, in consequence, acquire new professional competences. Higher differences between the countries involved students’ concerns about their career in the future rather than worries about personal finance. This can be explained by a varying and growing youth unemployment rate.
Keywords: student employment; COVID-19; GDP; youth unemployment rate.